2019
DOI: 10.1128/jvi.01464-18
|View full text |Cite
|
Sign up to set email alerts
|

The 11-Kilodalton Nonstructural Protein of Human Parvovirus B19 Facilitates Viral DNA Replication by Interacting with Grb2 through Its Proline-Rich Motifs

Abstract: Lytic infection of human parvovirus B19 (B19V) takes place exclusively in human erythroid progenitor cells of bone marrow and fetal liver, which disrupts erythropoiesis. During infection, B19V expresses three nonstructural proteins (NS1, 11-kDa, and 7.5-kDa) and two structural proteins (VP1 and VP2). While NS1 is essential for B19V DNA replication, 11-kDa enhances viral DNA replication significantly. In this study, we confirmed the enhancement role of 11-kDa in viral DNA replication and elucidated the underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…In addition, Southern blot analysis of Hirt DNA extracted from transfected cells showed that silent mutations of ISE3 in infectious clone M20 significantly decreased B19V DNA replication (by ϳ2.5-fold for the monomer replicative form [mRF] DNA) compared with the results seen with the counterpart WT M20 clone ( Fig. 8H and I), which was again in line with the previous observation that 11-kDa plays a role in viral DNA replication (38).…”
Section: Figsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, Southern blot analysis of Hirt DNA extracted from transfected cells showed that silent mutations of ISE3 in infectious clone M20 significantly decreased B19V DNA replication (by ϳ2.5-fold for the monomer replicative form [mRF] DNA) compared with the results seen with the counterpart WT M20 clone ( Fig. 8H and I), which was again in line with the previous observation that 11-kDa plays a role in viral DNA replication (38).…”
Section: Figsupporting
confidence: 90%
“…NS1 is the only viral protein that is essential for B19V DNA replication (35)(36)(37). However, the small nonstructural protein 11-kDa, which is localized predominantly in the cytoplasm and plays an enhancement role in viral DNA replication, is unique among parvoviruses (38). Mechanistically, the 11-kDa protein interacts with Grb2 (growth factor receptor bound protein 2) through the three SH3-binding motifs of the 11-kDa protein.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…pET30a-NP1 was constructed by inserting an NP1 ORF into the pET30a(ϩ) vector (EMD Millipore) through the NdeI and XhoI sites. pMBP-His was constructed by fusing 6ϫ histidines (His) to the maltose binding protein (MBP) ORF at the C terminus in pMAL-c5X (New England Biolabs) through the SacI site, as described previously (43).…”
Section: Discussionmentioning
confidence: 99%
“…Variants in RBM38 gene have not been reported so far. The RBM38 protein (coded by the RBM38 gene, 20q13.31, MIM * 612428) interacts with the intronic splicing enhancer 2 (ISE2) element of B19V pre-mRNA and promotes 11-kDa protein expression that regulates the 11-kDa protein-mediated augmentation of B19V replication [62]. The B19V-antibody complex enters the cells through an endocytosis process mediated by the direct interaction of antibody-bound complement factor C1q with its receptor CD93 on the cell surface [63].…”
Section: Parvovirus B19 and Myocarditis: Genetic Studies Unravel Molementioning
confidence: 99%